Long-Term Follow-Up of SAPHO Syndrome for 15 Years Led to a Diagnosis of Temporomandibular Joint Pain and Trismus - Koki Takamatsu; Hitoshi Sato; Takashi Moriya; Arisa Yasuda; Takaaki Kamatani; Tatsuo Shirota (Case Reports in Dentistry, 2021)
Synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome is a systemic disease with symptoms of pustular skin disease and sterile osteoarticular lesions. This disease rarely involves the temporomandibular joint (TMJ). Although it is a disease with a good long-term prognosis, its treatment remains challenging. We describe a case with long-term follow-up of SAPHO syndrome for 15 years in which TMJ pain and trismus led to the diagnosis. A 30-year-old woman with TMJ pain and trismus was referred to our department. Her medical history included palmoplantar pustulosis. Sterile inflammation in the left TMJ and diffuse sclerosing osteomyelitis of the mandible were observed. Thus, she was diagnosed with SAPHO syndrome. The symptoms of severe TMJ pain, trismus, and left cheek swelling presented three times in the 15 years. Symptomatic treatment with nonsteroidal anti-inflammatory drugs, antibiotics, corticosteroids, and bisphosphonates was administered several times. There has been no relapse of symptoms over the past nine years. The patient must be continuously kept under observation to look for the relapse of symptoms.